Development of Comic Learning Media Based on Critical Thinking for Elementary School Students - M. Arif Rahman; Nirwana Anas (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The purpose of education in the twenty-first century is to help students acquire critical thinking abilities, creativity and innovation , communication , dan collaboration however as seen by pupils’ poor critical thinking scores, this goal is really beginning to be disregarded. Another reality is that textbooks make learning less effective since they are stiff and boring, which makes pupils less interested in reading them. The goal of this project is to create comics that highlight critical thinking abilities in relation to changes in material form. Utilizing the Borg & Gall paradigm, research and development is the research methodology. According to the feasibility test findings, the practicality test yielded 88.8% of teacher replies and 90% of student responses in the very feasible category, while the feasibility level reached 89.2% from material experts, 92.6% from media experts, and a very viable category. Field test findings indicate that users find the generated comics to be engaging and motivating for learning. Using the N gain score formula, determine how well the product affects students’ critical thinking scores. The improvement criterion resulted in a gain score of 0.8 in the High category, with an average pretest score of 63.25 and an average posttest score of 92.2. According to research findings, using comic books that encourage critical thinking on the topic of substance changes as a teaching tool is a very realistic, useful, and successful way to enhance students’ understanding of science courses in SD/MI and to highlight the importance of critical thinking.